Small businesses : how they survice and succeed - "Clarke, Phillip" (Newton Abbot, 1973)
The public image of the small firm. Past disinterest and neglect. The new climate of interest. The Bolton Committe.The threat to small business and discrimination against it. Change and its effect on old attitudes and traditional markets. New oppurtunities for new-style entrepreneurs. The lack of research on small business. The arbitrariness of definitions of size. The common denominator : the owner-manager. Independnce and quality of life.
Keywords: Samll business